Correction: Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H. Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

Naringenin attenuates amiodarone-induced pulmonary fibrosis in rats via modulation of the SIRT1/NF-κB signalling pathway - Heba M. Arakeep; Wafaa Abdelaziz Emam; Amena Rezk Mohammed; Marwa H Sedira; Marwa Mahmoud Awad; Alshimaa Aboalsoud; Rehab Ahmed Ahmed El-Shaer; Azza Mostafa Mohammed Aboshanady; Norhan Ahmed AbuoHashish (Molecular Biology Reports, 2026)

In Vitro and In Silico Investigations of the Acaricidal Activity of Carvacrol Against Rhipicephalus annulatus - Samar M. Ibrahium; Abdel-Azeem S. Abdel-Baki; Fatma I. Abo El-Ela; Aliaa A. Balegh; Ahmed A. Wahba; Saleh Al-Quraishy; Ezzat M. Awad; Manal Ahmed; Wafaa G. Mahmoud; Shawky M. Aboelhadid (Acta Parasitologica, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Enhancing tomato plant immune responses through microbial bio-inducers against Pythium irregular root rot - Mohamed S. Attia; Mohamed M. Nofel; Amer M. Abdelaziz; Eslam K. Kandil; Abdulrahman E. Singer; Youssef E. Madkour; Mohammed G. Awad; Muostafa M. Abdelsamad; Abdullah A. Mahmoud; Hassan A. Rudayni; Amr Elkelish; Gharieb S. El-Sayyad (Physiological and Molecular Plant Pathology, 2026)

Genetic Diversity Analysis Using Start Codon Targeted (SCoT) and Sequence-Related Amplified Polymorphism (SRAP) Markers and Some Leaf Anatomical Traits in Sixteen Rutaceae Taxa - Mohamed A. Abdein; Samah O. Osman; Amr M. M. Mahmoud; Sahar A. M. Shamseldin; Mai M. Wahba; Sayed Y. Mohamed; Emadeldin A. H. Ahmed; Salwa El-Habashy; Rania A. E. Abdelzaher; Noha A. Sukar; Amany M. Mousa; Amal Ahmed Alyamani; et al. (Plant Molecular Biology Reporter, 2026)

Empagliflozin as a potential therapy for PCOS: Restoring hormonal balance and ovarian function in a letrozole-induced rat model - Heba A. Habib; Mahmoud El-Daly; Yahya I. Asiri; Saud Alqahtani; Eman M. Awad; Sara MN. Abdel Hafez; Al-Shaimaa F. Ahmed; Aliaa F. Anter (Tissue and Cell, 2026)

Utilization of free and immobilised potent lipase-producing bacteria for dual fat-oil-grease (FOG) degradation and sesame butter wastewater treatment - Cathbert Nomwesigwa; Mahmoud Nasr; Sameh Awad; Ahmed Abdel-Mawgood (International Biodeterioration & Biodegradation, 2026)

Alteplase versus tenecteplase in acute ischemic stroke with large vessel occlusion: a systematic review and meta-analysis - Mostafa Hossam El Din Moawad; Ibrahim Serag; Ahmed A. Abo Elnaga; Dina Essam Abo-elnour; Hamza A. Abdul-Hafez; Mohamed Ahmed Hammad; Lobna Ahmed Mohamed; Rawan Kamal Mohamed; Amir N. Attia; Abdelaziz A. Awad; Ibraheem M. Alkhawaldeh; Mahmoud Hegazy; et al. (European Journal of Clinical Pharmacology, 2026)

A comprehensive systematic review of randomized controlled trials on anesthetic agents in children’s upper gastrointestinal endoscopy: highlighting safety concerns and efficacy - Amr Elrosasy; Mahmoud Diaa Hindawi; Mohamed Abo Zeid; Abdelaziz A. Awad; Ahmed W. Abbas; Mohammad Al Diab Al Azzawi; Eslam Afifi; Ahmed Amgad; Mohamed Yasser; Khalid Sarhan; Sara Chikh Aissa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Upper gastrointestinal endoscopy (GIE) is essential for diagnosing and treating gastrointestinal disorders in children aged 6–12 years, yet it often requires sedation due to the significant discomfort and pain involved. We conducted a PRISMA 2020–compliant systematic review of randomized controlled trials (RCTs) from PubMed, Web of Science, Scopus, and Ovid (inception to March 30, 2024). Inclusion criteria are as follows: RCTs comparing sedative regimens (e.g., propofol, ketamine, remimazolam, dexmedetomidine) in children undergoing upper GIE. Exclusion criteria are as follows: non-RCTs, studies outside the age range, or non-English publications. Risk of bias was assessed using Cochrane ROB-2. Data were extracted for recovery time, hemodynamic parameters, and adverse events (hypoxia, bradycardia, dizziness). A systematic synthesis of outcomes was performed, with results presented descriptively and quantitatively (e.g., event rates, mean differences) to compare regimens. Nineteen RCTs were included with a total of 1955 patients. Propofol, either alone or in combination, was frequently used. The propofol-ketamine combination showed better hemodynamic stability (92.2 ± 16.8 bpm) compared to propofol-fentanyl (76.8 ± 13.8 bpm). S-ketamine demonstrated dose-dependent effects—0.3 mg/kg provided the shortest recovery time (33.5 min) with moderate dizziness (40.0%)—while 0.5 mg/kg offered optimal heart rate maintenance (93.81 bpm) but longer recovery (35.67 min) and increased dizziness (43.3%). The 0.7 mg/kg dose showed faster recovery than 0.5 mg/kg (33.5 vs 35.67 min), but the highest dizziness rates (73.3%). Post-procedural complications were minimal except for dose-dependent neurological effects with S-ketamine (visual disturbances peaking at 27.6% with 0.3 mg/kg). Remimazolam showed the fastest recovery overall. Adverse events varied by regimen: propofol-ketamine had higher hypoxia (6.8%) and dizziness (34.1%), while propofol-fentanyl showed more bradycardia (24.4%). Overall, remimazolam and dexmedetomidine regimens were linked to fewer complications, though they required careful monitoring for hypotension. However, heterogeneity in outcomes (e.g., recovery times, adverse events) underscores the need for individualized regimen selection. Limitations include variability in study designs and insufficient data on minimal effective doses. Further RCTs should standardize outcome measures and optimize dosing for children undergoing endoscopy.

Ameliorative effects of hesperidin against cyclophosphamide-induced ovarian dysfunction in the female rat model - Abdelmonem Awad Hegazy; Eman Ramadan Abd El Fattah; Marwa Mohamed Mahmoud Abdelfattah; Marwa M. Ahmad; Dalia Ibrahim Ahmed Mesallam; Samaa Salah Abd El-Fatah (Tissue and Cell, 2025)

Hydrogeophysical investigation for delineating groundwater aquifers in the Nabaa Al Hammara area, Wadi El Natrun, Egypt - SultanA.S. Araffa; Hassan H. El-Kadi; Abbas M. Abbas; Ahmed M. Al Dabour; Mahmoud S. Awad; Mahmoud Zayed (Journal of African Earth Sciences, 2025)

Depositional and diagenetic drivers of heterogeneous reservoir quality in the Neogene strata of the Red Sea (Egypt) - Ahmed Ali; Ahmed Awad Abdelhady; Ramadan S. A. Mohamed; Douaa Fathy; Mohamed Hashem; Mohamed S. Ahmed; Sherif M. Aboueldahab; Mahmoud M. Khalil; Mohamed H. Farag (Carbonates and Evaporites, 2025)

A deep deterministic policy gradient approach for optimizing feeding rates and water quality management in recirculating aquaculture systems - Wael M. Elmessery; Said Elshahat Abdallah; Awad Ali Tayoush Oraiath; Víctor Espinosa; Mohamed Fawzi Abdalshefie Abuhussein; Péter Szűcs; Mohamed Hamdy Eid; Doaa M. El-Shinawy; Huda Aljumayi; Samy F. Mahmoud; Abdallah Elshawadfy Elwakeel (Aquaculture International, 2025)
Optimizing feeding rates in recirculating aquaculture systems (RAS) is crucial for ensuring fish growth, health, and system efficiency. This research introduces a novel approach to RAS feeding control using a Deep Deterministic Policy Gradient (DDPG) reinforcement learning algorithm. The developed system integrates feeding rate optimization with comprehensive water quality management to improve overall performance and stability. The DDPG controller demonstrated superior tracking accuracy, reduced feed consumption, and improved operational stability compared to traditional control methods such as Model Predictive Control (MPC), PID, and Bang-Bang control. The learned policy-maintained feeding rates within optimal ranges while adapting to dynamic system requirements and environmental conditions. The integration of water quality monitoring and control further enhanced system stability, ensuring critical parameters remained within target ranges. Comparative analysis revealed the DDPG controller’s advantages in terms of faster recovery times after environmental perturbations, improved long-term stability, and significant economic benefits through reduced operational costs and increased efficiency. The robustness and adaptability of the system were validated through comprehensive testing under various fault conditions, growth phases, and system scales. The successful development and evaluation of the DDPG-based RAS feeding control system represents a significant advancement in aquaculture management. The demonstrated improvements in efficiency, stability, and economic performance establish the potential for this approach to revolutionize feeding practices in commercial RAS operations. Further research and development efforts can build upon these findings to advance the state-of-the-art in intelligent aquaculture management systems and promote the sustainability and profitability of the industry.

Thermal decomposition behavior and kinetics for pyrolysis and catalytic pyrolysis of sugarcane bagasse - Mohamad Awad El-Naggar; Mahmoud Ahmed Mousa; S.M. Reda; Mahmoud Mohamed Emara (Sustainable Chemistry and Pharmacy, 2025)

Curating Benzothiophene Experimental Absorption and Emission Spectra to Design Fluorescent Organic Polymer Chemical Space: A Machine Learning Quest - Shaimaa H. Mallah; Azal S. Waheeb; Abrar U. Hassan; Masar A. Awad; Ayad R. Jalfan; Ashraf Y. Elnaggar; Islam H. El Azab; Mohamed H. H. Mahmoud (Journal of Fluorescence, 2025)

Application of Biostimulants Alleviated Drought Stress in Sugar Beet (Beta vulgaris L.) by Improving Oxidative Defense System, Osmolytes Accumulation and Root Yield - Abdul Sattar; Ahmed Abou El-Yazied; Basmah M. Alharbi; Hany G. Abd El-Gawad; Zahid Khorshid Abbas; Karima Mohamed El-Absy; Samy F. Mahmoud; Mohammed M. Althaqafi; Doaa Bahaa Eldin Darwish; Nadi Awad Al-Harbi; Qasim Ali; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)

Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)
Due to water shortages and the potential impact of Ethiopia’s new dam on the Nile River, Egypt is seeking new water resources. This study assesses the drinking water quality and associated risks from potentially toxic elements (PTEs) in the Quaternary aquifer (QA) in Beni-Suef, Egypt. Using a comprehensive approach, including PHREEQC geochemical modeling, ionic ratios, multivariate statistical analyses, and the integrated weight water quality index (WQI), the study evaluated the sources of ion contamination and the mixing of Nile water with QA. Various indices, such as the Heavy Metal Pollution Index (HPI), ecological Risk Index (RI), Hazard Quotient (HQ), and Hazard Index (HI), were used to assess ecological and health risks. Monte Carlo simulations provided probabilistic assessments of non-carcinogenic risks for adults and children. GIS tools were used to map risk indices, identifying the most deteriorated locations for sustainable management. The hydrochemical analysis revealed water facies including Na–Cl, Ca–Mg–HCO 3 , and mixed types, influenced by carbonate dissolution, ion exchange, and silicate weathering. Contamination sources, particularly in the north and south, were linked to agricultural activities, irrigation return flow, municipal waste, and evaporation. The WQI indicated that 10.14% of samples were extremely poor, 21.7% were poor, 26% were medium, and 42% were good to excellent. PTE contamination varied, with HPI values indicating good water quality in the central area in 53.6% of the collected samples (HPI < 30), but contamination in the north and south is high (HPI > 51). Ecological Risk Index values were below the threshold in 100% of samples (RI < 30), confirming water safety regarding PTEs. In comparison, for hazard index (HI) through oral/ingestion, adults exhibited HI values ranging from 0.012 to 2.16, while children showed higher values, ranging from 0.045 to 8.25. However, the hazard index for oral/ingestion exceeded safe limits in the north and south (HI oral > 1), posing non-carcinogenic risks. Monte Carlo simulations revealed significant risks from oral exposure to manganese (HQ oral > 1), particularly in El-Wasta and El-Fashn, necessitating further treatment and management.

Atorvastatin loaded lecithin-coated zein nanoparticles based thermogel for the intra-articular management of osteoarthritis: in-silico, in-vitro, and in-vivo studies - Heba Amin Elgendy; Amna M. A. Makky; Yara E. Elakkad; Heba H. Awad; Mahmoud A. El Hassab; Nihal Farid Younes (Journal of Pharmaceutical Investigation, 2024)
Purpose Up-to-date literature offers limited data about utilizing atorvastatin calcium (ATV) as a promising chondroprotective agent in osteoarthritis (OA). So, this study aims to develop a depot intra-articular (IA) delivery system for ATV to enhance its deposition in the articular joint. Methods A 3 3 D-optimal design was implemented to prepare ATV-loaded lecithin-coated zein nanoparticles. The optimized formulation (Opt-LCZN) was selected and imaged using a transmission electron microscope according to the desirability value. Various in-vitro and in-silico studies were conducted to evaluate the features of Opt-LCZN. Additionally, it was loaded into an injectable thermogel (Opt-LCZN-thermogel) and evaluated in-vivo in OA-induced Sprague Dawley rats. Results The Opt-LCZN showed entrapment efficiency of 70.00 ± 2.96%, particle size of 191.95 ± 17.42 nm, zeta potential of − 20.12 ± 0.79 mV, and polydispersity index of 0.25 ± 0.01. The docking studies revealed favorable binding of zein and ATV, confirmed by molecular dynamics simulation. The morphological examination displayed a bilayer spherical structure formed of a zein core enclosed by a lecithin coat. Furthermore, the formulated Opt-LCZN-thermogel achieved a remarkable sustained release profile, with nearly 50% of the drug being released over 144 h. Opt-LCZN-thermogel showed a significant reduction in inflammation in OA-induced rats, confirmed by knee joint swelling and knee bend test results, in addition to the pro-inflammatory and anti-inflammatory mediators’ levels. The protective effect of ATV can be markedly observed through histopathological examination. Conclusion Based on these outcomes, the formulated IA delivery system of ATV can be presented as an excellent candidate for ameliorating OA. Graphical abstract

Magnetic separation, sunlight-driven photocatalytic activity, and antibacterial studies of Sm-doped Co0.33Mg0.33Ni0.33Fe2O4 nanoparticles - Amani Aridi; Mariam Rabaa; Malak Mezher; Daoud Naoufal; Mahmoud I. Khalil; Ramadan Awad (Environmental Science and Pollution Research, 2024)

Depositional facies controls on reservoir rock typing and heterogeneity: Devonian siliciclastic succession, south central Ghadames basin, Libya - Mahmoud Leila; Essam El-Khoriby; Mohammed Awad Ahmed; Omar Saied; Hanaa El Adl (Marine and Petroleum Geology, 2024)

Evaluation of the subsurface structural features of the Farafra Oasis, western desert, Egypt using aeromagnetic data - Mohamed M. Khalifa; Waheed H. Mohamed; Mahmoud A. El Ammawy; Ayman I. Taha; Ahmed Awad; Ahmed Awad Orchid (Modeling Earth Systems and Environment, 2024)

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Evaluating the effect of Spirulina platensis on the immune response of broiler chickens to various vaccines and virulent Newcastle disease virus challenge - Ashraf M. Awad; Mahmoud E. Sedeik; Ahmed H. Salaheldin; Raghda I. Goda; Nahed A. El-Shall (Research in Veterinary Science, 2023)

Prospects of resistance of some Sudanese tomato accessions to South American tomato pinworm, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) and its mechanism - Elharith H. Bakheit; Awad K. Taha; Mohammed E. E. Mahmoud; Telal S. Abdelhalim; Khitma A. S. Mustafa; El Tahir I. Mohamed; Eltayeb Abdellateef (International Journal of Tropical Insect Science, 2023)

Neuromodulatory effect of vardenafil on aluminium chloride/d-galactose induced Alzheimer’s disease in rats: emphasis on amyloid-beta, p-tau, PI3K/Akt/p53 pathway, endoplasmic reticulum stress, and cellular senescence - Heba H. Awad; Mahmoud A. Desouky; Alaa Zidan; Mariam Bassem; Amaal Qasem; Mona Farouk; Haidy AlDeab; Miral Fouad; Cherry Hany; Nada Basem; Rita Nader; Ashrakat Alkalleny; et al. (Inflammopharmacology, 2023)
Dysregulation of protein homeostasis, proteostasis, is a distinctive hallmark of many neurodegenerative disorders and aging. Deleteriously, the accumulation of aberrant proteins in Alzheimer’s disease (AD) is accompanied with a marked collapse in proteostasis network. The current study explored the potential therapeutic effect of vardenafil (VAR), a phosphodiesterase-5 inhibitor, in AlCl 3 / d -galactose ( d -gal)-induced AD in rats and its possible underlying mechanisms. The impact of VAR treatment on neurobehavioral function, hippocampal tissue architecture, and the activity of the cholinergic system main enzymes were assessed utilizing VAR at doses of 0.3 mg/kg and 1 mg/kg. Additionally, the expression level of amyloid-beta and phosphorylated tau proteins in the hippocampus were figured out. Accordingly, VAR higher dose was selected to contemplate the possible underlying mechanisms. Intriguingly, VAR elevated the cyclic guanosine monophosphate level in the hippocampus and averted the repressed proteasome activity by AlCl 3 / d -gal; hence, VAR might alleviate the burden of toxic protein aggregates in AD. In addition, a substantial reduction in the activating transcription factor 6-mediated endoplasmic reticulum stress was demonstrated with VAR treatment. Notably, VAR counteracted the AlCl 3 / d -gal-induced depletion of nuclear factor erythroid 2-related factor 2 level. Moreover, the anti-senescence activity of VAR was demonstrated via its ability to restore the balance of the redox circuit. The modulation of phosphatidylinositol-3-kinase/protein kinase B/p53 pathway and the reduction of nuclear factor kappa B level, the key regulator of senescence-associated secretory phenotype mediators release, with VAR treatment were also elucidated. Altogether, these findings insinuate the possible therapeutic benefits of VAR in AD management. Graphic abstract

Comparable bio-evaluation of curcumin and chitosan-encapsulated curcumin nanoparticles against the reprotoxic potential of fenpropathrin pyrethroid in rats: Genomic and morphometric prospectives - Amany Abdel-Rahman Mohamed; Amany Behairy; Yasmina M. Abd El-Hakim; Mohamed M.M. Metwally; Tarek Khamis; Samah S. Abuzahrah; Ahmed E. Abdelhamid; Leena S. Alqahtani; Walaa M. Essawi; Badriyah S. Alotaibi; Manal Alosaimi; Rehab Ahmed Ahmed El-Shaer; et al. (Food and Chemical Toxicology, 2023)

The Paleocene climate in west central Sinai (Egypt): insights from the calcareous nannofossils - Mahmoud Faris; Manal Shabaan; Ahmed Awad Abdelhady; Mohamed S. Ahmed; Fatma Shaker (Arabian Journal of Geosciences, 2023)

Fe-Co spinel oxides supported UiO-66-NH2 derived zirconia/ N-dopped porous hollow carbon as an efficient oxygen reduction reaction electrocatalyst - Soliman Gamal; Doaa A. Kospa; Mahmoud M. Kaid; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Journal of Environmental Chemical Engineering, 2023)

Magnetic Signature of Gold Deposits: Example from Um Garayat Region, South Eastern Desert, Egypt - Mohamed Mostafa Gobashy; Mahmoud M. Mekkawi; Sultan Awad Sultan Araffa; Moahmed M. Ezz Eldin; Mohamed Hassan Khalil (Pure and Applied Geophysics, 2023)
Magnetic methods of exploration have proved to be efficient and have potential in the gold mineralization industry. New magnetic processing technologies aid in improving the process of interpretation and gold opportunity identification. In this work, we show the possible application of combined digital magnetic filters to explore new gold mineralization localities with application to a well-known Au mineralization zone. Um Garayat (UG) region, southeastern desert, Egypt, is an ancient example of a potential area for gold mining. Modern analysis showed that other types of mineral concentrations are present. So, exploiting the magnetic signature of the area for future investment is of great interest. The old UG gold mine is characterized by volcanic and tectonic features such as faulting and folding that affect the arc sedimentary rock sequence of repeated deformation stages. A thorough geophysical effort has been carried out around the old gold mine in the UG area to explore the extension of mineralized ore deposits. A detailed geophysical survey using magnetics was carried out in this study together with the available aeromagnetic data. Field data sets on appropriate sites were measured, processed, and evaluated by suitable software. High magnetic anomalies were detected based on grid filter analysis and contact occurrence maps as marked as possible ore deposits after satisfying the geologic conditions for gold formation. An integrated understanding of attained results revealed that the new possible ore deposits are related directly to fault and fracture zones in the shape of lenses of variable thickness in this zone. Results show that newly detected mineral occurrences in the UG area are also controlled by major faults and hydrothermal solution enrichment along fault zones at a depth ranging from 20 to 70 m. Favorable fault/joint mineralized places were located. The relationship between the Au-quartz vein's strike direction compared with magnetic anomaly lineament analysis was studied. Search for new sources of Au and other mineral deposits in addition to quartz veins is needed as pockets of accumulated mineral-rich rock fragments are deposited in drainage wadis and fault/joint zones because of hydrothermal solution enrichment.

Using the Flocculation Index to optimise coagulant dosing during drinking water treatment - Mahmoud Khedher; John Awad; Erica Donner; Barbara Drigo; Rolando Fabris; Martin Harris; Kalan Braun; Christopher W.K. Chow (Journal of Water Process Engineering, 2023)

Anticancer activity of chicken cathelicidin peptides against different types of cancer - Maged Mostafa Mahmoud; Modhi Alenezi; Ahmed M. Al-Hejin; Turki S. Abujamel; Fadwa Aljoud; Abdulwahab Noorwali; Ibrahim A. Awad; Mohammed Alkhaled; Haitham A. Yacoub (Molecular Biology Reports, 2022)

Does ramadan fasting affect the therapeutic and clinical outcomes of warfarin? a systematic review and meta-analysis - Eslam Mohammed Rabea; Kirellos Said Abbas; Dina M. Awad; Nancy H. Elgoweini; Amro Ahmed El-Sakka; Nada H. Mahmoud; Basel Abdelazeem (European Journal of Clinical Pharmacology, 2022)

Vulnerability of tourism to climate change on the Mediterranean coastal area of El Hammam–EL Alamein, Egypt - Esraa A. El-Masry; Mahmoud Kh. El-Sayed; Mohamed A. Awad; Amr A. El-Sammak; Mohamed A. El Sabarouti (Environment, Development and Sustainability, 2022)

Synoptic characteristics of rainy winters over the northern Arabian Peninsula - Mana Ali Asiri; Mansour Almazroui; Abdulhaleem Hussin Labban; Adel Mahmoud Awad (Arabian Journal of Geosciences, 2021)

Biochemical and microbiological characteristics of some Mediterranean salted fish products - Adel A. A. Mohdaly; Awad A. Mahmoud; Mohamed Fawzy Ramadan; Mohamed H. H. Roby (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Integrated geophysical approach in exploration of iron ore deposits in the North-eastern Aswan-Egypt: a case study - Mahmoud Mohamed. Mekkawi; Ahmed ElKotb. ElEmam; Ayman Ismail. Taha; Mohamed AbdelSabour. Al Deep; Sultan Awad Sultan. Araffa; Usama Saad. Massoud; Abbas Mohamed. Abbas (Arabian Journal of Geosciences, 2021)

Secreted protein of Ly6 domain 1 enhanced bovine trophoblastic cell migration activity - Mahmoud Awad; Keiichiro Kizaki; Toshina Ishiguro-Oonuma; Toru Takahashi; Kazuyoshi Hashizume (In Vitro Cellular & Developmental Biology - Animal, 2020)

Composition and radioactivity of Oligocene fossil bones and their country rocks in Gabal Qatrani, Fayoum, Egypt - Ahmed El-Kammar; Mohamed El-Sankary; Ashraf El-Azab; Mahmoud Awad (Arabian Journal of Geosciences, 2020)

ECONOMIC ASSESSMENT OF DUYRIDGE DAM AS A WATER‐HARVESTING SCHEME IN IRAQ - Shayma Al‐Rubaye; Wadaq Awad; Safa Ahmed; Aisha Mahmoud (Irrigation and Drainage, 2020)
Iraq, home of the Tigris and Euphrates rivers, has survived an extreme deficiency of surface water assets over the years. The gap is due to the decline of the Iraqi water share every year, as well as a high demand for water use from different sectors, particularly agriculture. Dam development has long given significant economic benefits to Iraq in circulating low‐priced electricity and supporting low‐income farmers by supplying them with a free irrigation system (Zakaria et al, 2012). This encouraged domestic consumption and investment. Despite the fact that numerous advantages are expected from dam construction, it should be painstakingly assessed, utilizing cost–benefit analysis before endorsement. This study aims to evaluate the capability of the Duyridge Dam in Maysan Governorate to harvest rainwater in Iraq and meet the local populations' needs as well as the geological, topographic, hydrological and economic requisites of water. The result indicates that the net present costs and net present benefits at a 10% discount rate are equal to US$18.8 million and US$20.2 million respectively, while the net present value is equal to US$179 000 and the benefit–cost ratio is equal to 1.08. Likewise, the results show that the internal rate of return is 11% and the payback of the project period is 5 years. The sensitivity analysis of the dam was estimated as well. © 2020 John Wiley & Sons, Ltd.

Genetic diversity among snake melon landraces ( Cucumis Melo Var. Flexuosus ) using molecular descriptors - Muhanad Akash; Nisreen Awad; Mahmoud Kasrawi (Plant Biosystems, 2020)

Correction to: Potential toxicity of trace elements and nanomaterials to Chinese cabbage in arsenic- and lead-contaminated soil amended with biochars - Yasser Mahmoud Awad; Meththika Vithanage; Nabeel Khan Niazi; Muhammad Rizwan; Jörg Rinklebe; Jae E. Yang; Yong Sik Ok; Sang Soo Lee (Environmental Geochemistry and Health, 2019)

Potential toxicity of trace elements and nanomaterials to Chinese cabbage in arsenic- and lead-contaminated soil amended with biochars - Yasser Mahmoud Awad; Meththika Vithanage; Nabeel Khan Niazi; Muhammad Rizwan; Jörg Rinklebe; Jae E. Yang; Yong Sik Ok; Sang Soo Lee (Environmental Geochemistry and Health, 2019)

Short-term biochar application induced variations in C and N mineralization in a compost-amended tropical soil - Shih-Hao Jien; Wen-Chi Chen; Yong Sik Ok; Yasser Mahmoud Awad; Chien-Sen Liao (Environmental Science and Pollution Research, 2018)

Cytotoxic activity evaluation and molecular docking study of phenolic derivatives from Achillea fragrantissima (Forssk.) growing in Egypt - Basma M. Awad; Eman S. Habib; Amany K. Ibrahim; Amira S. Wanas; Mohamed M. Radwan; Mohamed A. Helal; Mahmoud A. ElSohly; Safwat A. Ahmed (Medicinal Chemistry Research, 2017)

Phenotypic and Genotypic Characterization of Bacteriocinogenic Enterococci Against Clostridium botulinum - Awad A Shehata; Reda Tarabees; Shereen Basiouni; Mahmoud Gamil; Ahmed S Kamal; Monika Krüger (Probiotics and Antimicrobial Proteins, 2017)

Interactive effects of biochar and polyacrylamide on decomposition of maize rhizodeposits: implications from 14C labeling and microbial metabolic quotient - Yasser Mahmoud Awad; Johanna Pausch; Yong Sik Ok; Yakov Kuzyakov (Journal of Soils and Sediments, 2017)

Effects of biochar and polyacrylamide on decomposition of soil organic matter and 14C-labeled alfalfa residues - Yasser Mahmoud Awad; Sang Soo Lee; Yong Sik Ok; Yakov Kuzyakov (Journal of Soils and Sediments, 2017)

Sedimentology and reservoir characterization of the Upper Miocene Qawasim Formation, El-Tamad Oil Field onshore Nile Delta, Egypt - Mahmoud Leila; Mahmoud Ahmed Kora; Mohamed Awad Ahmed; Abdelhakim Ghanem (Arabian Journal of Geosciences, 2016)

Isolation and full genome characterization of avian influenza subtype H9N2 from poultry respiratory disease outbreak in Egypt - Awad A. Shehata; Rokshana Parvin; Hesham Sultan; Mohamed Y. Halami; Shaimaa Talaat; Alaa Abd Elrazek; Mahmoud Ibrahim; Kristin Heenemann; Thomas Vahlenkamp (Virus Genes, 2015)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)

Detection of New Point Mutations of BRCA1 and BRCA2 in Breast Cancer Patients - Moufida Bensam; Elsayed Hafez; Doaa Awad; Muhammad El-Saadani; Mahmoud Balbaa (Biochemical Genetics, 2014)

Lateral variations of coda Q and attenuation of seismic waves in the Gulf of Suez, Egypt - Mamdouh A. Morsy; Sherif El Hady; Salah M. Mahmoud; Enayat Abdel Moneim Awad (Arabian Journal of Geosciences, 2013)

Phytochemical and in vitro screening of some Ficus and Morus spp. for hypolipidaemic and antioxidant activities and in vivo assessment of Ficus mysorensis (Roth) - Nagwa E. Awad; Ahmed A. Seida; Manal A. Hamed; Ahlam H. Mahmoud; Marwa M. Elbatanony (Natural Product Research, 2012)

Hydrogeophysical study of the El Qaa Plain, Sinai, Egypt - Sultan Awad Sultan; Mahmoud Ismail Mohameden; Fernando M. Santos (Bulletin of Engineering Geology and the Environment, 2009)